The Influence of Social Media and Experiential Marketing on Customer Loyalty in MSMEs in the Fashion Sector at Sentra Distro Trunojoyo Bandung - Rahayu, Novi Kadarini (STIE Ekuitas, 2024)
Introduction/Main Objectives: Intense competition across industries makes customer loyalty vital for the survival of businesses, including MSMEs. However, MSMEs often struggle with limited resources. The rapid advancement of information technology, especially social media, presents significant opportunities for these businesses to broaden their reach and engage more closely with customers. In this context, experiential marketing emerges as an effective strategy to create memorable experiences that enhance customer loyalty. Background Problems: Many fashion MSMEs in Sentra Distro Trunojoyo Bandung have yet to fully leverage social media, particularly in creating engaging content. Customer loyalty is a valuable asset that not only drives repeat purchases but also promotes the brand. Novelty: Previous studies have predominantly focused on large companies or MSMEs in other sectors. This study uniquely focuses on fashion MSMEs, which have distinct market dynamics and customer interactions. It also reveals that while social media has great potential, its suboptimal use can negatively affect customer loyalty. Research Methods: The study employs a quantitative descriptive method to analyze the impact of social media and experiential marketing on customer loyalty among fashion MSMEs at Sentra Distro Trunojoyo Bandung. Convenience sampling was used to select a sample of 100 respondents from the research population. Data were collected using a questionnaire and analyzed through descriptive and statistical methods with SPSS 27. Finding/Results: List the empirical finding(s) and write a discussion in one or two sentences. Conclusion: The study concludes that experiential marketing is crucial for boosting customer loyalty in fashion MSMEs at Sentra Distro Trunojoyo Bandung. Conversely, poorly optimized social media usage can harm customer loyalty, making experiential marketing more effective in fostering loyalty than less targeted social media efforts.